Arthurian literature XXXVI : sacred space and place in Arthurian romance - Bowden, Sarah; Friede, Susanne; Hammer, Andreas (Arthurian Literature Ser., 2021)
Arthurian Literature has established its position as the home for a great diversity of new research into Arthurian matters. It delivers fascinating material across genres, periods, and theoretical issues.